Interfaith Marriage and Its Legal Implications for Children from the Perspective of Maqashid Sharia - Fachri Wahyudi; Vera Charmila (Journal of Southeast Asian Islam and Society, 2022)
Interfaith marriages have long occurred in Indonesia, both openly and secretly in various circles of society (in various social dimensions). Although it has long occurred in Indonesia, it does not mean that the problem of interfaith marriage is accepted and considered normal, even this problem produces various controversies and rejection among the community. One of the problems arising from interfaith marriage is the issue of offspring or their children. The psychological development of children born to parents who have the same religion will certainly be different from the psychology of children born to parents who have different religions. This research is characterized by library research where all sources of data are taken from written references related to the topics discussed. The research is descriptive analytic, as for the primary sources in this research include: Islamic law, Law No. 1 of 1974 concerning marriage, Compilation of Islamic Law (KHI). The secondary sources in this research are books on Islamic marriage law in Indonesia. Data analysis of this research uses an inductive approach, namely taking general conclusions from specific conclusions. The results of the study explain that children born to parents of different religions will experience many problems, disturbed and threatened by the dharuriyat needs of the child until it leads to the implications that will be borne by children born to parents of different religions, including inheritance rights and guardianship of marriage which will certainly be very detrimental to the child in the future